Gestão dos recursos naturais na Guiné-Bissau : política de governança dos recursos florestais nos municípios de Cacheu e São Domingos - Mendes, Hipólito (2020)
Thus, the governance policy model came up with the idea of democratizing processes based on cooperativism between the State and civil society, focusing on the strategy developed in development that includes the public interested in seeking to solve common social problems. This dissertation aimed to evaluate the governance system of natural resources, based on the analysis of the evolution of the loss of tree cover, in the municipalities of Cacheu and São Domingos, in Guinea-Bissau, taking into account the determining factors of the loss of tree cover, mainly anthropogenic. The use of remote data from the Global Forest Watch (GFW) platform is a feasible way to detect and monitor the occurrence of vegetation suppression, thus ensuring consistency in the observation of statistical data in the study territory. The integration of these two theories allowed a better perception on the subject addressed, in the same way it made it possible to unveil the relevant aspects about the framework of the natural resources governance system, and the collateral damage resulting from negative externalities, the loss of biomass and CO2 emissions. The results of the study demonstrate that plant suppression has evolved in a divergent way between both municipalities. In the municipality of Cacheu, there was a decrease from 2013 to 2018, while the municipality of São Domingos experienced continuous growth until 2018. From the analysis of the governance characteristics of common resources, it became evident that the process of deforestation, in the municipality of São Domingos, took place due to the expansion of the cashew culture for economic purposes. It should be noted that the cashew nut is destined for international markets, through commercialization by intermediary companies, which are not responsible for the harmful environmental effects. In addition, it was possible to analyze the profile of deforestation and fire occurrences in the two municipalities. With regard to deforestation, the months of November and December, the wet season, recorded more occurrences in both municipalities. While fires, in the dry period, in the months of May and June, registered more occurrences. This result indicates that more comprehensive international coordination measures on exports from areas at risk are necessary to solve the environmental degradation linked to cashew fruit growing in Guinea-Bissau.